2018
DOI: 10.1111/chd.12612
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable cardiovascular risk factors in adolescents and adults with congenital heart disease

Abstract: A low proportion of individuals with CHD are in ideal cardiovascular health, suggesting a need to promote healthy lifestyles during adolescence and throughout adulthood in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Moons et al reported that almost 80% of patients with congenital heart disease had at least one cardiovascular risk factor, despite a young age of the patients (median age: 26 years) . Additionally, Harris et al reported that only approximately 30% of adolescents and adults with congenital heart disease were in ideal cardiovascular health …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moons et al reported that almost 80% of patients with congenital heart disease had at least one cardiovascular risk factor, despite a young age of the patients (median age: 26 years) . Additionally, Harris et al reported that only approximately 30% of adolescents and adults with congenital heart disease were in ideal cardiovascular health …”
Section: Discussionmentioning
confidence: 99%
“…Patients with congenital heart disease have been reported to have a high prevalence of cardiovascular risk factors, with almost 80% of patients having at least one cardiovascular risk factor . Decreased glucose tolerance on oral glucose tolerance test (OGTT) is more common in patients with complex ACHD compared with healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity has been steadily increasing over the past decades [8] and the trend is similar in patients with CHD (9,10,15). Recent studies using the American dataset [9] and the Canadian CHD registry [17] found no difference in overweight and obesity rates between CHD and non-CHD paediatric populations. In a recent cohort study, the rates of metabolic syndrome were similar between adults with CHD and healthy control subjects [18].…”
Section: Proportion Of Underweight Overweight and Obesity Over Timementioning
confidence: 99%
“…Physical activity is known to decrease adiposity and BMI, and markers of stress and chronic inflammation, and to mitigate the association between stress and adiposity in otherwise healthy children [51][52][53][54]. Physical activity has similar health benefits in children with CHD [16,40,[55][56][57]; thus early stress experienced by children with CHD may underlie findings of elevated waist circumference, and weaker associations between physical activity and waist circumference. The theory is compelling that there exists a cascade whereby early physical and psychological stress leads to elevated inflammation and cortisol, which drives elevated abdominal fat accrual, further contributing to inflammation and vascular alteration, which cannot be fully offset by physical activity, and ultimately leading to increased cardiovascular disease risk.…”
Section: A Mechanistic Link Between Waist Circumference and Cardiovasmentioning
confidence: 99%